The Effect of Model Intervention Towards the Intention of Early Detection of Cervical Cancer with Via Test - Sondang Sidabutar1, Santi Martini2, Rachmat Hargono (Indian Journal of Forensic Medicine & Toxicology, 2020)
The purpose of this study was to evaluate the woman of childbearing age decision’s model towards the intention of early detection of cervical cancer with the VIA (visual inspection with acetic acid) test. The design was quasi-experimental. The population of women of childbearing age and sample size was 70. Technique Paired samples statistics. Statistical analysis using the Wilcoxon test with a probability of 0.05. The difference in the value of the pre and post test were seen from the difference in the mean value between the pre and post test. In the treatment group, the difference test results were significant between the pre and post test, the value of p = 0,000. In Control group, the results of the difference test were not significant between the pre and post test, the value of p > 0.05. The Decision Model was a new finding of research where have the highest level of situation awareness on the situation, events and dynamics of its health condition. The decision model showed that with a high level of awareness, the women decided to make early detection of cervical cancer supported by high self efficacy and intention.